Can human amblyopia be treated in adulthood? - Astle, Andrew T.; McGraw, Paul V.; Webb, Ben S. (Taylor & Francis, 2011)
Amblyopia is a common visual disorder that results in a spatial acuity deficit in the affected eye. Orthodox treatment is to occlude the unaffected eye for lengthy periods, largely determined by the severity of the visual deficit at diagnosis. Although this treatment is not without its problems (poor compliance, potential to reduce binocular function, etc) it is effective in many children with moderate to severe amblyopia. Diagnosis and initiation of treatment early in life are thought to be critical to the success of this form of therapy. Occlusion is rarely undertaken in older children (more than 10 years old) as the visual benefits are considered to be marginal. Therefore, in subjects where occlusion is not effective or those missed by mass screening programs, there is no alternative therapy available later in life. More recently, burgeoning evidence has begun to reveal previously unrecognized levels of residual neural plasticity in the adult brain and scientists have developed new genetic, pharmacological, and behavioral interventions to activate these latent mechanisms in order to harness their potential for visual recovery. Prominent amongst these is the concept of perceptual learning—the fact that repeatedly practicing a challenging visual task leads to substantial and enduring improvements in visual performance over time. In the normal visual system the improvements are highly specific to the attributes of the trained stimulus. However, in the amblyopic visual system, learned improvements have been shown to generalize to novel tasks. In this paper we ask whether amblyopic deficits can be reduced in adulthood and explore the pattern of transfer of learned improvements. We also show that developing training protocols that target the deficit in stereo acuity allows the recovery of normal stereo function even in adulthood. This information will help guide further development of learning-based interventions in this clinical group.